2018
DOI: 10.1039/c7fo01258f
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial effects of Cirsium japonicum var. maackii on menopausal symptoms in ovariectomized rats

Abstract: In women, menopause refers to a series of physiological and mental symptoms of distress that result from a decrease in 17β-estradiol. In addition to the loss of fertility, the symptoms include facial flushing, depression, osteoporosis, sexual dysfunction, and genitourinary atrophy. Cirsium japonicum var. maackii is a perennial herbaceous species found in the mountains and fields of Korea, China, and Japan. The medicinal uses of C. japonicum include antioxidant, antidiabetic, antitumor, antifungal, and anti-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 35 publications
3
12
0
Order By: Relevance
“…The present finding showed that there's no significant different between Sham group and OVX in case of serum calcitonin level. The same finding was reported by Park [21] that in ovariectomized rats there was no significantly different serum calcitonin level compared to normal rats. But the trends of calcitonin level in this research shows increased calcitonin level along with increment of nicotine dose.…”
Section: Discussionsupporting
confidence: 89%
“…The present finding showed that there's no significant different between Sham group and OVX in case of serum calcitonin level. The same finding was reported by Park [21] that in ovariectomized rats there was no significantly different serum calcitonin level compared to normal rats. But the trends of calcitonin level in this research shows increased calcitonin level along with increment of nicotine dose.…”
Section: Discussionsupporting
confidence: 89%
“…2016; Park et al . 2018). The increased adiposity in ovariectomized rats might be explained by the malfunction of the appetite‐controlling hormone leptin and oestrogen depletion as, normally, oestrogen participates in modulation of energy homeostasis by direct action on central appetite and energy‐regulating pathways (Torto et al .…”
Section: Discussionmentioning
confidence: 99%
“…2016; Park et al . 2018). The body weight of the rats started to increase from week 4 of the study and the appetite of the rats was affected since week 2 in all the ovariectomized groups, which indicated that depleted oestrogen levels could affect the body metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…In our previous research works, we have shown that compounds 1 and 2 from CJM confer potential therapeutic effects against diabetes, as indicated by its strong inhibitory effects on the polyol pathway which is a major mechanism linked to the pathogenesis of diabetic complications [13,19]. Moreover, compounds 1-3 in CJM has also been reported to exhibit beneficial against menopausal symptoms in animal models [18]. Moreover, the results showed that although CJ and CJM belong to the same species, the two varieties showed distinct flavonoid contents in that all three methoxyflavones were present in CJM whereas 2 was absent in CJ.…”
Section: Resultsmentioning
confidence: 99%
“…maackii (CJM) [13,14]. These compounds have been shown to exhibit bioactive properties, and thus have pharmacological importance [15][16][17][18]. Accordingly, the aim of this study was to determine the distribution of these compounds and quantify their contents in selected Korean thistles by high performance liquid chromatography (HPLC) with ultraviolet-visible detection.…”
Section: Introductionmentioning
confidence: 99%